2016
DOI: 10.1080/00224499.2016.1252308
|View full text |Cite
|
Sign up to set email alerts
|

Caught in a “Bad Romance”? Reconsidering the Negative Association Between Sociosexuality and Relationship Functioning

Abstract: Sociosexuality refers to individual differences in interest and willingness to engage in sexual activity without an emotional connection. Unrestricted sociosexuality is associated with a greater likelihood of infidelity and with poorer relationship quality. However, previous research has failed to examine relationship-specific characteristics that may moderate these findings. Two studies of romantically involved adults examined whether relationship commitment and different relationship agreement types moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 45 publications
5
53
0
Order By: Relevance
“…That individuals within CNM relationships report a faster life history makes sense in light of previous research on the association between faster life histories and promiscuous mating systems. CNM individuals' preference for multiple sexual and romantic partners has been documented across several samples (Morrison et al, 2013;Rodrigues et al, 2016Rodrigues et al, , 2017Rodrigues et al, , 2019Mogilski et al, 2017Mogilski et al, , 2019Balzarini et al, 2018b) and is replicated again in this study using an alternative measure of sociosexuality (i.e., the MMSO) that separately measures affinity toward short-and long-term partnerships. We found that those in multi-partner relationships reported a more STMO than those in open and monogamous relationships, and open individuals reported a more STMO than monogamous people.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…That individuals within CNM relationships report a faster life history makes sense in light of previous research on the association between faster life histories and promiscuous mating systems. CNM individuals' preference for multiple sexual and romantic partners has been documented across several samples (Morrison et al, 2013;Rodrigues et al, 2016Rodrigues et al, , 2017Rodrigues et al, , 2019Mogilski et al, 2017Mogilski et al, , 2019Balzarini et al, 2018b) and is replicated again in this study using an alternative measure of sociosexuality (i.e., the MMSO) that separately measures affinity toward short-and long-term partnerships. We found that those in multi-partner relationships reported a more STMO than those in open and monogamous relationships, and open individuals reported a more STMO than monogamous people.…”
Section: Discussionsupporting
confidence: 63%
“…People may generally assume that individuals within CNM relationships possess faster life history traits, but it is currently unknown whether these perceptions are accurate. People in CNM relationships consistently report a more unrestricted sociosexuality (Morrison et al, 2013;Rodrigues et al, 2016Rodrigues et al, , 2017Rodrigues et al, , 2019Mogilski et al, 2017Mogilski et al, , 2019Balzarini et al, 2018b). However, it is possible that they do not possess other fast life history qualities that interfere with the long-term, cooperative values endorsed by slow life history strategists.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of gender, sociosexually unrestricted individuals are more likely to engage in extradyadic online or face-to-face interactions (e.g., Martins et al, 2016), and extradyadic sex (e.g., Barta & Kiene, 2005;Rodrigues, Lopes, & Smith, 2017), and to indicate less relationship satisfaction (Rodrigues, Lopes, & Pereira, 2016;Webster et al, 2015) and relationship commitment (Foster, Shrira, & Campbell, 2006;Rodrigues, Lopes, & Pereira, 2017). Moreover, those with past experience of extradyadic sex are also more likely to repeat such behavior in future relationships (Knopp et al, 2017).…”
Section: Introductionmentioning
confidence: 99%